👤

a -3:(x×2)=1 b -x+4=1 c -2x +16=10 d 4x+3=2x-8 e -8x+7=-4-4​

Răspuns :

Răspuns:

Explicație pas cu pas:

-3:(x×2)=1

x×2 = -3 : 1 = -3

x = -3/2

____________

-x+4=1

x = 4 - 1 = 3

____________

-2x +16=10

2x = 16 - 10 = 6

x = 6/2 = 3

____________

4x+3=2x-8

3x - 2x = -8 - 3

x = -11

______________

-8x+7=-4-4​

8x = 7 + 4 + 4 = 15

x = 15/8

Răspuns:

a) -3:(x×2)=1

2x=-3:1

x=-3/2=>x=-1,5

b) -x+4=1

-x=1-4

-x=-3=>x=3

c) -2x +16=10

-2x=10-16

-2x=-6

x=6/2=>x=3

d) 4x+3=2x-8

4x-2x=-8-3

2x=-11=>x=-11/2

e) -8x+7=-4-4​

-8x=-8-7

-8x=-15=>x=15/8